FI’L MUDLĀRI’ MABNIYY (VERBA IMPERVEKTUM PERMANENT) DALAM AL-QUR’AN JUZ 1-15 (ANALISIS SINTAKSIS) (Universitas Negeri Semarang, 2023)
The permanent impervektum verb in Arabic tradition is called fi’l mudlāri’ mabniyy (فعل المضارع المبني), namely the imperfect verb that meets two nūn taukid (tsaqilah or khafifah) direcly and nūn niswah. The purpose of this study is to increase knowledge of permanent impervectum verbs (fi’l mudlāri’ mabniyy) in the Qur’an. This researchis a qualitative research with library research design. The data is in the form of fi’l mudlāri’ mabniyy with the source of the Qur’an juz 1-15. The instruments used are data cards and recapitulation sheets. And technical data analysis using intralingual equivalents. Data collection techniques using the documentation method. The results of this study indicate that in the Qur’an chapters 1-15 found 112 data, based on the type of fi’l mudlāri’ mabniyy (cause mabniyy) there are 101 data because they met nūn taukid tsaqilah, 1 data for meeting nūn taukid khafifah and 10 data for meeting nūn niswah. Based on the mabniyy of fi’l mudlāri’, 102 data with mabniyy fatchah and 10 data with mabniyy sukūn. Based on the i’rab machal, there are 74 data with raf’ (بمحل الرفع), 5 data based on nashab (بمحل النصب), 33 data based on jazm (بمحل الجزم).